Pengaruh Kesadaran Pajak dan Persepsi Mahasiswa terhadap Minat Berlangganan Spotify setelah Pengenaan PPN Digital - Bujangga Ayu Chitra Paramita; I Nyoman Gede Arya Diatmika (ManBiz: Journal of Management and Business, 2025)
This study aims to examine the influence of tax awareness and student perceptions on the interest in subscribing to Spotify following the implementation of Digital VAT in the South Denpasar region, based on the Theory of Planned Behavior. This quantitative research utilized a purposive sampling method to collect data from 120 active students through online questionnaires, which were subsequently analyzed using multiple linear regression. The results indicate that, partially, tax awareness has a positive and significant effect on subscription interest, suggesting that an understanding of tax functions strengthens students' intention to continue using official services. Similarly, student perceptions of Digital VAT have a positive and significant influence, showing that a favorable view of policy fairness and transparency helps maintain user loyalty. Simultaneously, both tax awareness and student perceptions significantly influence the variation in Spotify subscription interest. This study concludes that adequate tax literacy and positive perceptions of government policy are key factors in maintaining consumer interest within the digital service ecosystem among academics.